Macroecology of methane‐oxidizing bacteria: the β‐diversity of pmoA genotypes in tropical and subtropical rice paddies. (1st August 2013) - Lüke, Claudia; Frenzel, Peter; Ho, Adrian; Fiantis, Dian; Schad, Peter; Schneider, Bellinda; Schwark, Lorenz; Utami, Sri Rahayu
Summary Studies addressing microbial biogeography have increased during the past decade, but research on microbial distribution patterns is still in its infancies, and many aspects are only poorly understood. Here, we compared the methanotroph community in paddy soils sampled in Indonesia, Vietnam, China and Italy, focusing on the distance–decay relationship. We used the pmoA gene as marker for methanotroph diversity in terminal restriction fragment length polymorphism, microarray and pyrosequencing approaches. We could observe a significant increase of β‐diversity with geographical distance across continents (12 000 km). Measured environmental parameters explained only a small amount of data variation, and we found no evidence for dispersal limitation. Thus, we propose historical contingencies being responsible for the observed patterns. Furthermore, we performed an in‐depth analysis of type II methanotroph pmoA distribution at the sequence level. We used ordination analysis to project sequence dissimilarities into a three‐dimensional space (multidimensional scaling). The ordination suggests that type II methanotrophs in paddy fields can be divided into five major groups. However, these groups were found to be distributed in all soils independent of the geographic origin. By including tropical field sites (Indonesia and Vietnam) into the analysis, we further observed the first paddy fields harbouring a methanotroph community depleted in type II methanotrophs.